Whole-Rock Elemental and Sr-Nd Isotope Geochemistry and Petrogenesis of the Miocene Elmadağ Volcanic Complex, Central Anatolia (Ankara, Turkey) - Kürşad Asan (Geosciences, 2020)
This study presented whole-rock elemental and Sr-Nd isotope geochemistry data with the purpose to decipher the origin and evolution of the Miocene Elmadağ Volcanic Complex, Central Anatolia (Ankara, Turkey). Volcanic products spanned in composition from mildly alkaline basaltic (47–52 wt% SiO2) and medium- to high-K calc-alkaline intermediate (54–62 wt% SiO2; andesite to trachyandesite) to felsic (64–74 wt% SiO2; dacite to rhyolite) units. Despite a homogeneous major element composition, basaltic rocks were characterized by two distinct trace element and isotopic signatures, which have been correlated with different mantle sources. The first group of basaltic rocks was similar to those of oceanic island basalts (OIB) and was derived from asthenospheric mantle source. The second group had geochemical characteristics of orogenic basalts derived from subduction-modified lithospheric mantle source and represented parental magma of the intermediate to felsic rocks. By coupling geochemical and textural analyses of the rocks from the Elmadağ Volcanic Complex, I suggest that crystallization of olivine + clinopyroxene + apatite played an important role in the evolution of basaltic rocks, while plagioclase + amphibole + apatite + Fe-Ti oxides ± zircon crystallization was major process involved in the evolution of intermediate to felsic rocks. The EVC basaltic rocks were associated with the post-collisional extensional tectonic regime in the Central Anatolia, but the coexistence of the OIB-like volcanism implies variations in the extension dynamics during Miocene.